Desempenho perceptivo-auditivo em crianças com e sem transtorno fonológico na classe das oclusivas - Assis, Mayara Ferreira de [UNESP]; Cremasco, Elissa Barbi Mouro Pagliari [UNESP]; Silva, Lídia Maurício da; Berti, Larissa Cristina [UNESP] (FapUNIFESP (SciELO), 2021)
PURPOSE: To compare the auditory-perceptual performance of children with and without phonological disorder (PD) in the identification task of contrasts between stops phonemes. METHODS: Information was selected from a database regarding the auditory-perceptual performance of 46 children (23 with a diagnosis of PD with involvement in the stops (G1) and 23 with typical speech development (G2)), aged 4 and eight years old, in an identification task of the class of stops consonants in Brazilian Portuguese, using the speech perception assessment instrument (PERCEFAL). The reaction time, the number of errors and correctness, as well as the pattern of perceptual error were considered in the analysis. RESULTS: Regarding the auditory-perceptual accuracy, T-Test showed a statistically significant difference, in which typical children had a higher average of correctness than children with PD and shorter reaction time for correct answers. Regarding the error pattern, repeated measures ANOVA showed a significant effect for the group and error pattern, but not for the interaction between group and error pattern. Tukey's Post Hoc test showed for both groups that errors involving place of articulation were superior to voicing and voicing + place of articulation errors. CONCLUSION: children with phonological disorders have worse accuracy in relation to children without disorders and, also, longer response time for correctness. Errors involving the place of articulation between the stops were the most frequent for both groups.

OBJETIVO: Comparar o desempenho perceptivo-auditivo de crianças com e sem transtorno fonológico (TF) na tarefa de identificação dos contrastes entre os fonemas oclusivos. MÉTODO: Foram selecionadas, de um banco de dados, informações referentes ao desempenho perceptivo-auditivo de 46 crianças (23 com diagnóstico de TF com acometimento nas oclusivas (G1) e 23 com desenvolvimento típico de fala (G2)), entre quatro e oito anos de idade, em uma tarefa de identificação na classe das consoantes oclusivas do Português Brasileiro, a partir do instrumento de avaliação de percepção de fala (PERCEFAL). O tempo de reação, os números de erros e acertos, bem como o padrão de erro perceptual foram considerados na análise. RESULTADOS: Com relação à acurácia perceptivo-auditiva o Test-T mostrou uma diferença estatisticamente significante, em que as crianças típicas tiveram uma média de acerto maior do que as crianças com TF e um tempo de reação menor para os acertos. No tocante ao padrão de erro a ANOVA de medidas repetidas mostrou um efeito significativo para o grupo e padrão de erro, mas não para a interação entre grupo e padrão de erro. O teste Post Hoc de Tukey mostrou para ambos os grupos que os erros envolvendo ponto articulatório foram superiores aos erros de vozeamento e vozeamento + ponto articulatório. CONCLUSÃO: crianças com transtorno fonológico apresentam pior acurácia em relação às crianças sem alteração e, ainda, um maior tempo de resposta para os acertos. Erros envolvendo o ponto de articulação entre as oclusivas foram os mais frequentes em ambos os grupos.
Auditory-perceptual performance in children with and without phonological disorder in the stops class